An analysis of Thought Presentation in Hemingway’s A Farwell to Arms - batool abdulmohsin miri (Journal of Research in Social Science and Humanities, 2025)
A crucial component of literary works is the depiction of dialogue, written communication, and the introspective thoughts of characters or individuals. This research aims to investigate the portrayal of thoughts in Hemingway's novel, A Farewell to Arms. To this end, a comprehensive examination of various methods of presenting thoughts is conducted in relation to Short Leech's (2007) framework. Four separate examples have been purposefully picked with the objective of studying the stylistic depiction of thoughts in Hemingway's novel, A Farewell to Arms. The excerpts are chosen based on the probable stylistic characteristics of the discourse categories. Two passages are selected from Book I, and two excerpts are chosen from Book II of the novel. The inquiry determined that A Farewell to Arms is told only from the perspective of the protagonist, Henry Fredric, via his consciousness. The study has prioritized the classification of thought presentation rather than speech presentation. Furthermore, the narrative is mostly conveyed via the use of three distinct categories: free indirect thought, direct thought, and free direct thought. During discussions, the dominant modes of communication are direct thought and free direct thought.